Scullery appliances.co "Multipurpose scissors" / Emalyn Damyra Idza Azizul Izham...[et al.] - Azizul Izham, Emalyn Damyra Idza; Mohd Yuslan, Nur Alia Syafieqa; Abdul Rahman, Nur Fatihah; Mohd Yusof Zaki, Nurul Nadiah (2016)
Scullery Appliances.co is introducing a new scissor with the invention and idea of multipurpose. A multipurpose scissor is introduced to ease the work of labour in the kitchen spent by housewives and people who lives alone. This scissor comes with a detachable blade that hence fulfils the idea of multipurpose as different blade comes with different uses. A normal blade shows the use of common scissor while the serrated blade is the multipurpose scissor being introduced. This multipurpose scissor comes with the function of descaling fishes, to cut through hard shells, comes with a bottle opener and may act as knife too when detached. The advantages of the scissor is it save space, cost, time and easy to use. Together in this report marketing aspects is included regarding the price, expected market growth, target customer as well the marketing strategy. This is to ensure that our product is eligible and valid to be in the current market despite fierce competition.